Does physical activity moderate the association between device-measured sedentary time patterns and depressive symptoms in adults? - Werneck, André O. (2022)
Objectives: To investigate the association between sedentary time (ST) patterns and depressive symptoms, and whether moderate-to-vigorous physical activity (MVPA) can moderate this association. Methods: This cross-sectional study included a representative sample of 243 adults (mean age 41.8616.7 years, 56.4% women) from a city in Southeast Brazil. Depressive symptoms were estimated through the Hospital Anxiety and Depression Scale (HADS). ST patterns (i.e., number of breaks, mean length of sedentary bouts, and number of long sedentary bouts), total ST, and MVPA were assessed using accelerometers. Results: Poisson regression models revealed associations of total ST (b = 0.063; 95%CI 0.011 to 0.116) and number of long bouts (0.108; 0.047 to 0.171) with depressive symptoms among men. MVPA moderated the associations of breaks and longer bouts of ST with depressive symptoms, with an increase of one break/hour, the increase of one long bout, and a decrease of 1 minute in mean bout length being associated with a reduction of 0.211 and increases of 0.081 and 0.166, respectively, in the number of depressive symptoms among men with physical inactivity (breaks =-0.211;-0.360 to-0.063; mean bout length = 0.081; 0.003 to 0.158; number of long bouts = 0.166; 0.090 to 0.242). Conclusions: Interventions that encourage breaking up ST should be helpful to reduce depressive symptoms among people with physical inactivity. Clinical trial registration: ClinicalTrials.gov (NCT03986879).